The Association of Service Quality with Patient Satisfaction and Loyalty: a Cross-Sectional Path Analysis in a Pediatric Outpatient Clinic - Arib Balma, Hammam; Rochani Mulyani, Sri; Rulia, Rulia; Nugroho, Taufan; Paramarta, Vip (Cv. Syntax Corporation Indonesia, 2025)
The quality of service is consistently related to patient satisfaction and loyalty in children's health services, where clinical competence must be balanced with the delivery of responsive, patient-centered services. Examining the relationship between service quality and patient loyalty through patient satisfaction at the Children's Polyclinic of Ananda Lubuklinggau Mother and Child Hospital (RSIA). This study is a cross-sectional survey of 100 patients/parents of patients (purposive sampling; May–June 2025) using validated instruments for service quality (based on SERVQUAL), patient satisfaction (based on PSQ derivatives), and patient loyalty (6 statements). Descriptive analysis and path analysis were carried out using SPSS version 29. All constructs were rated in the